2021
DOI: 10.1186/s12877-020-01980-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the positive outcomes of discharge planning interventions for older adults hospitalized following a fall: a realist synthesis

Abstract: Background Older adults hospitalized following a fall often encounter preventable adverse events when transitioning from hospital to home. Discharge planning interventions developed to prevent these events do not all produce the expected effects to the same extent. This realist synthesis aimed to better understand when, where, for whom, why and how the components of these interventions produce positive outcomes. Methods Nine indexed databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(235 reference statements)
0
6
0
3
Order By: Relevance
“…In Stockholm, there were coordinators designated to manage the hospital discharge planning, which in previous research has shown to facilitate a good discharge process [18,19]. This was not brought up as a facilitator, but this might be because all our participants from the hospital had this role and did not reflect upon them self as a facilitator for the discharge process.…”
Section: Organisation Of the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In Stockholm, there were coordinators designated to manage the hospital discharge planning, which in previous research has shown to facilitate a good discharge process [18,19]. This was not brought up as a facilitator, but this might be because all our participants from the hospital had this role and did not reflect upon them self as a facilitator for the discharge process.…”
Section: Organisation Of the Systemmentioning
confidence: 99%
“…Carefully planned and performed discharges have also the potential to improve both patients' quality of life [16] and satisfaction with the process [17]. Providing a coordinator designated to manage the hospital discharge planning has shown to facilitate the process, however, this is often not standard [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, apesar de evidenciados os benefícios obtidos a partir do envolvimento do paciente, cuidadores e familiares no processo de planejamento da alta, os relatos dos participantes demonstram dificuldades de inseri-los na elaboração das ações, consonante a uma revisão narrativa que destaca falas de cuidadores não envolvidos nas tomadas de decisão (9) . Diversos estudos destacam a insatisfação dos utentes de saúde e cuidadores responsáveis sobre a falha de comunicação com os profissionais prestadores da assistência durante o planejamento da alta e transição dos cuidados (9,(17)(18) .…”
Section: Processo De Alta Domiciliar Processo De Alta Domiciliarunclassified
“…As orientações devem abranger todas as questões e dificuldades, adequadas aos aspectos socioculturais e retomadas. Além disso, é importante instruir quanto às possibilidades de complicações e direcionamento do cuidado em quadros de urgência (18) . Aspectos influentes na efetivação da alta pelos Aspectos influentes na efetivação da alta pelos serviços de AD serviços de AD Nessa categoria, foi possível reconhecer alguns aspectos que interferem no processo de elaboração e planejamento da alta.…”
Section: Processo De Alta Domiciliar Processo De Alta Domiciliarunclassified
“…Furthermore, falls in older age significantly impact healthcare and related costs all over the world [ 13 ]. After a fall, seniors experience indeed long hospitalizations, complex treatments, thus needing resource-intensive care, including rehabilitation and home care [ 24 , 25 ], in addition to effective discharge planning interventions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%